Institucionalización de la Hidrología Médica en España - Rodríguez Sánchez, Juan Antonio (Anales de Hidrología Médica, 2007)
The factors which forgathered to make Medical Hydrology a speciality were quite different from tose ones in other disciplines linked to hospital and technological development. From this perspective, its process of professionalization was more frequently stressed by individual participations from prower (creation of a Cuerpo de Médicos-Directores de Baños, of a University Chair or a Research Institute) rather than the needs and actions of those who committed to balneological clinic. The legitimization guidelines imposed were far from the reality of the spa, incapable of getting adapted to its evolution and inefficient in the conciliation between companies and doctors. Its paradoxical effect was to undermine the associative and scientific development of this speciality.
Keywords: Medical hydrology; Mineral waters; Hydrotherapy; Balneological research; Professionalization; Specialization; Medical education; 19th-20th centuries history